Nghiên cứu chiết xuất phytosterol từ phụ thải công nghiệp dầu đậu tương. - Huy, Lưu Đức; Diệp, Nguyễn Thị; S., Savinova T.; V., Lukasev N.; P., Beletskaya I. (Vietnam Journal of Chemistry, 2012)
In this article we present a technical method for the isolation of a phytosterol mixture from the by-product of soybean oil production  with about 4 - 5% yield and more than 90% purity. The phytosterol mixture product is examined by physical methods such as IR and HPLC-MS.